2018
DOI: 10.1038/s41377-018-0007-z
|View full text |Cite|
|
Sign up to set email alerts
|

Multi-functional bismuth-doped bioglasses: combining bioactivity and photothermal response for bone tumor treatment and tissue repair

Abstract: Treatment of large bone defects derived from bone tumor surgery is typically performed in multiple separate operations, such as hyperthermia to extinguish residual malignant cells or implanting bioactive materials to initiate apatite remineralization for tissue repair; it is very challenging to combine these functions into a material. Herein, we report the first photothermal (PT) effect in bismuth (Bi)-doped glasses. On the basis of this discovery, we have developed a new type of Bi-doped bioactive glass that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
101
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 271 publications
(104 citation statements)
references
References 48 publications
3
101
0
Order By: Relevance
“…A significant portion of tissue engineering research focuses on the ability to derive native biological structures as biomaterials for regenerative purposes [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 ]. Biomimetic structures, in particular, strive to recreate naturally regenerative microenvironments to promote desired cell behavior and mitigate inflammatory responses [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…A significant portion of tissue engineering research focuses on the ability to derive native biological structures as biomaterials for regenerative purposes [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 ]. Biomimetic structures, in particular, strive to recreate naturally regenerative microenvironments to promote desired cell behavior and mitigate inflammatory responses [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Biological tissue penetration experiments were also carried out to display the potential of PersL in bioimaging . The pork was chosen to simulate tissues, and 2 mm thick skin, fat, and lean plate samples were designed.…”
Section: Resultsmentioning
confidence: 99%
“…The classical metal nanomaterials have generated great interest because of their excellent photothermal conversion performance in anticancer therapies. It has been reported that bismuth-doped BG scaffolds displayed high photothermal conversion efficiency to induce hyperthermia for osteosarcoma treatment 60 . Meanwhile, multiple kinds of metal oxide nanoparticles have been used as photoabsorbers to kill cancer cells.…”
Section: Discussionmentioning
confidence: 99%